Abordagens sustentáveis para a drenagem e o manejo de águas pluviais urbanas: uma análise a partir dos planos municipais e dos profissionais da Bacia Hidrográfica do Tietê-Jacaré, SP (UGRHI-13) - Negro, Giovana Spinelli (2024)
With the increase in extreme events resulting from climate change and their consequences (flooding, inundation, and erosion processes), combined with sanitation practices and the logic of stormwater management, new approaches to sustainable urban drainage and rainwater management have emerged. This study analyzed advancements in these approaches within master plans, sectoral plans, and other urban policy instruments across the 34 municipalities that comprise UGRHI 13, a study area selected due to the implementation of the Programa de Drenagem Sustentável e Revitalização de Rios Urbanos (Sustainable Drainage and Urban Rivers Revitalization Program). The research also examined municipal professionals’ perspectives on the current context and potential changes in approaches to urban drainage and sustainable rainwater management in municipalities within the Tietê-Jacaré Hydrographic Basin. To achieve this, municipal documents were reviewed to identify laws, drainage policies, and public administrative structures supporting sustainable drainage and rainwater management initiatives, along with their interrelations and impacts across the 34 municipalities. Additionally, five municipalities — Araraquara, Dois Córregos, Lençóis Paulista, Pederneiras, and São Carlos—were selected for interviews with career public servants from sectors related to urban drainage. These interviews aimed to analyze challenges and explore potential pathways for transitioning to sustainable urban drainage models. In the analysis of municipal plans, principles of sustainable urban drainage and rainwater management were identified in 30 out of 113 documents, spanning 17 of the 34 municipalities in UGRHI 13. Among the excerpts related to these principles, 26 potential instruments for implementing non-conventional paradigms in drainage and rainwater systems stood out. The interviews also revealed specific but fragmented progress in adopting sustainable approaches to drainage and rainwater management systems. Several challenges were highlighted, including the lack of design standards and maintenance protocols for sustainable drainage techniques, limited funding to implement actions, insufficient training for involved professionals, and the workload burden on these professionals, which often renders sustainable approaches unfeasible or difficult to implement. The interviews also suggested actions to address these barriers. In conclusion, the study found that sustainable approaches to drainage and rainwater management are already being pursued in the UGRHI 13 municipalities, supported by both professionals and related public policies.